A study on the association between early-pregnancy hair metal levels and gestational diabetes mellitus - Feng Tang; Jun Guo; Li-An-Sheng Wu; Xiao-Yuan Fan; Han-Wen Zhang; Noora Kartiosuo; Boris Novakovic; Ting-Li Han; Hua Zhang; Yin-Yin Xia; Philip Baker; Richard Saffery (Environmental Pollution, 2026)

Coprinus comatus filtrate extract, a novel neuroprotective agent of natural origin - Maja Karaman; Kristina Tesanovic; Aleksandra Novakovic; Dragica Jakovljevic; Ljiljana Janjusevic; Filip Sibul; Boris Pejin (Natural Product Research, 2020)

Correction to: Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)

Rewiring of glucose metabolism defines trained immunity induced by oxidized low-density lipoprotein - Samuel T. Keating; Laszlo Groh; Kathrin Thiem; Siroon Bekkering; Yang Li; Vasiliki Matzaraki; Charlotte D. C. C. van der Heijden; Jelmer H. van Puffelen; Ekta Lachmandas; Trees Jansen; Marije Oosting; L. Charlotte J. de Bree; et al. (Journal of Molecular Medicine, 2020)
Stimulation of monocytes with microbial and non-microbial products, including oxidized low-density lipoprotein (oxLDL), induces a protracted pro-inflammatory, atherogenic phenotype sustained by metabolic and epigenetic reprogramming via a process called trained immunity . We investigated the intracellular metabolic mechanisms driving oxLDL-induced trained immunity in human primary monocytes and observed concomitant upregulation of glycolytic activity and oxygen consumption. In two separate cohorts of healthy volunteers, we assessed the impact of genetic variation in glycolytic genes on the training capacity of monocytes and found that variants mapped to glycolytic enzymes PFKFB3 and PFKP influenced trained immunity by oxLDL. Subsequent functional validation with inhibitors of glycolytic metabolism revealed dose-dependent inhibition of trained immunity in vitro. Furthermore, in vivo administration of the glucose metabolism modulator metformin abrogated the ability for human monocytes to mount a trained response to oxLDL. These findings underscore the importance of cellular metabolism for oxLDL-induced trained immunity and highlight potential immunomodulatory strategies for clinical management of atherosclerosis. Key messages Brief stimulation of monocytes to oxLDL induces a prolonged inflammatory phenotype. This is due to upregulation of glycolytic metabolism. Genetic variation in glycolytic genes modulates oxLDL-induced trained immunity. Pharmacological inhibition of glycolysis prevents trained immunity.

New aurone epoxide and auronolignan from the heartwood of Cotinus coggygria Scop - Miroslav Novakovic; Iris Djordjevic; Nina Todorovic; Snezana Trifunovic; Boban Andjelkovic; Boris Mandic; Milka Jadranin; Ivan Vuckovic; Vlatka Vajs; Slobodan Milosavljevic; Vele Tesevic (Natural Product Research, 2019)

Antioxidant volatiles of the freshwater bryozoan Hyalinella punctata - Boris Pejin; Djura Nakarada; Miroslav Novakovic; Vele Tesevic; Aleksandar Savic; Ksenija Radotic; Milos Mojovic (Natural Product Research, 2014)